“Modelado para desarrollar la motricidad fina en los niños de Educación Inicial’’ - Quinte Allaica, Janeth Estefania (2024)
The present research comprehensively addresses motor development in Early Childhood Education, highlighting the role of art as a pedagogical tool to enhance fine motor skills during this crucial stage of learning in children from Early Childhood Education in the province of Cotopaxi, Pujilí Canton, Tingo la Esperanza Parish. The main objective of the research is to design a manual of clay infant characters to promote the development of fine motor skills in Early Childhood Education children. The proposed methodology for the manual's development is based on constructivist principles, which posit that learning is an active and meaningful process built through interaction with the environment and reflection on experiences. The Clay Character Manual "The Realm of Fantasy" is presented, aimed at facilitating the development of fine motor skills in children in Initial Education. This manual consists of a cover, an introduction, and multiple stories that include details such as title, duration, objectives, materials, photographs, step-by-step instructions for creating the main figures, and their corresponding evaluation. The incorporation of modeling as a strategy to improve fine motor skills in early education is crucial for stimulating both physical and cognitive development in children from a young age. Therefore, the need to implement artistic clay modeling to stimulate fine motor skills in children in Initial Education levels I-II is concluded.